2006
DOI: 10.1186/1471-2164-7-164
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic discovery of microRNA precursors from human ESTs and introns

Abstract: Background: MicroRNAs (miRNAs) function in many physiological processes, and their discovery is beneficial for further studying their physiological functions. However, many of the miRNAs predicted from genomic sequences have not been experimentally validated to be authentic expressed RNA transcripts, thereby decreasing the reliability of miRNA discovery. To overcome this problem, we examined expressed transcripts -ESTs and intronic sequences -to identify novel miRNAs as well as their target genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…The GC content and ch_ratio are within the range given by Li et al (2006) and Barozai et al (2008) [21,27].…”
Section: Sequence and Structural Features Filtermentioning
confidence: 89%
See 2 more Smart Citations
“…The GC content and ch_ratio are within the range given by Li et al (2006) and Barozai et al (2008) [21,27].…”
Section: Sequence and Structural Features Filtermentioning
confidence: 89%
“…To validate the miRNAs through the sequence and structural features filter, the GC content, Core mfe, hairpin mfe and Ch_ratio were calculated as described by Li et al, (2006) [27] with a little modification for Core mfe calculation, as described by Barozai et al, (2008) [21]. The mfe for core and hairpin structures were calculated by MFOLD (version3.2) [26] publicly available at http://www.bioinfo.rpi.edu/applications/mfold/ rna/form1.cgi.…”
Section: Sequence and Structural Features Filtrationmentioning
confidence: 99%
See 1 more Smart Citation
“…When one would like to know the orientation of predicted miRNA, a specialized algorithm such as this may help. The prediction performances of Berezikov et al (2005), miRNAMap (Hsu et al 2006), RNAmicro (Hertel and Stadler 2006), and Li et al (2006) are also shown in Figure 4. The data on miRNAs predicted by those methods were obtained from the respective investigators' Web sites, with the exception of RNAmicro.…”
Section: Genome Scanning and Comparison With Other Methodsmentioning
confidence: 99%
“…RNAmicro (Hertel and Stadler 2006) predicts miRNAs from multiple sequence alignments using a support vector machine (SVM) based on several types of evolutionary and secondary structural features calculated from the multiple alignments. Li et al (2006) have predicted miRNAs from human expressed sequence tags and introns. In their analysis, a sequence and structural filter is first applied, and then a conservation filter is used to find miRNA candidates.…”
Section: Introductionmentioning
confidence: 99%